New progresses on cell surface protein HSPA5/BiP/GRP78 in cancers and COVID-19 - Li, Ting; Fu, Jiewen; Cheng, Jingliang; Elfiky, Abdo A.; Wei, Chunli; Fu, Junjiang (Frontiers in Immunology, 2023)
Heat-shock-protein family A (Hsp70) member 5 (HSPA5), aliases GRP78 or BiP, is a protein encoded with 654 amino acids by the HSPA5 gene located on human chromosome 9q33.3. When the endoplasmic reticulum (ER) was stressed, HSPA5 translocated to the cell surface, the mitochondria, and the nucleus complexed with other proteins to execute its functions. On the cell surface, HSPA5/BiP/GRP78 can play diverse functional roles in cell viability, proliferation, apoptosis, attachments, and innate and adaptive immunity regulations, which lead to various diseases, including cancers and coronavirus disease 2019 (COVID-19). COVID-19 is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, which caused the pandemic since the first outbreak in late December 2019. HSPA5, highly expressed in the malignant tumors, likely plays a critical role in SARS-CoV-2 invasion/attack in cancer patients via tumor tissues. In the current study, we review the newest research progresses on cell surface protein HSPA5 expressions, functions, and mechanisms for cancers and SARS-CoV-2 invasion. The therapeutic and prognostic significances and prospects in cancers and COVID-19 disease by targeting HSPA5 are also discussed. Targeting HSPA5 expression by natural products may imply the significance in clinical for both anti-COVID-19 and anti-cancers in the future.